Synchronous and asynchronous tools use evaluation in the agricultural sciences traning processes (2016)
Distance education has achieved a great advance in recent years, thanks to the Information and Communications Technology —lCTs— tools incorporation. These communication tools can be classified as synchronous and asynchronous, the first ones are those in which their users” groups are interconnected at the same time and establish a communication processes in real time, the second ones allow interaction and communication at different moments, so the participation of the partners is not required to be at the same time.These tools use in six courses of agricultural sciences of the Universidad Nacional Abierta y a Distancia —UNAD— was evaluated. The results demonstrated that the use of synchronous tools is low, although students prefer them (55.7 %), and think they facilitate a greater interaction with their faculty and peers. Their main limitation is the requirement to be at a specific timetable for their interaction and connection, besides that in some cases due to connectivity difficulties.